Demographic and Mental Health Factors Associated with Pathological Dissociation in a Portuguese Sample - Espirito-Santo, Helena (2013)
Pathological dissociation has been extensively studied in many countries; however, little is known about it in Portugal. This research examined the role of demographic variables and mental health on dissociation in Portugal. We assessed 505 participants from 6 samples consisting of dissociative patients (n = 37), conversive patients (n = 26), somaticizing patients (n = 59), posttraumatic stress disorder patients (n = 50), other psy- chiatric patients (n = 174), and nonclinical subjects (n = 159). Dissociation was measured by Portuguese versions of the Dissociative Experiences Scale and Somatoform Dissociation Questionnaire; the LEAD procedure and subscales of the Brief Symptom Inventory indicated mental health. Pathological psychological dissociation was significantly more frequent in women, in the youngest of the participants, and in those with less education. Multiple logistic regression revealed that psychoticism, paranoid ideation, and depression symptoms made both men and women more vulnerable to psychological dissociation. Furthermore, psychological dissociation was more probable in men having symptoms of obsession and paranoid ideation and in women having symptoms of psychoticism and paranoid ideation. Pathological somatoform dissociation was significantly more probable in women with less education. Moreover, somatoform dissociation was more likely in women with somatization symptoms and more likely in men with symptoms of somatization and psychoticism. Even though significant associations were found, causal relations could not be established because the study was cross-sectional.